Recovery of Small Quantities of Viruses from Clean Waters on Cellulose Nitrate Membrane Filters - Berg, Gerald (1971)
A method is described for quantitatively recovering small amounts of viruses from large volumes of buffered, distilled water. Development of the method was motivated by the anticipated need for testing large volumes of renovated sewage for viruses. The method consists of adsorbing viruses onto cellulose nitrate membrane filters (0.45 μm pore size) from water containing sufficient Na(2)HPO(4) to produce a molarity of 0.05 and sufficient citric acid to produce a pH of 7, and eluting the adsorbed viruses in 3% beef extract under extended sonic treatment. Complete recovery of poliovirus 1, echovirus 7, and coxsackievirus B3 resulted when less than 100 plaque-forming units were added to 1-liter quantities of water. Recoveries of reovirus 1 were almost as good. Preliminary studies indicate that good recoveries can be made from 25-gal quantities of water. The method described is efficient in waters of high quality and may be useful for recovering viruses in renovated, and perhaps in tap waters, but not in waters containing certain organic matter unless that matter is first removed.